Aplicacion de un tratamiento silvicultual experimental en el bosque de La Lupe, Rio San Juan, Nicaragua - Sabogal, C.; Castillo, A.; Mejia, A.; Castañeda, A. (Centro Agronómico Tropical de Investigación y Enseñanza, 2001)
This document describes the application on experimental scale of a silvicultural treatment in a forest selectively logged by a timber company in the humid tropics of Nicaragua. Based on a diagnostic sampling in the La Lupe experimental forest, a silvicultural treatment was designed consisting in the liberation of future harvest trees through the elimination of competitors by stem girdling and poisoning. Plots for treatment and 1 ha-permanent sampling plots were established in the experimental area of 15,36 ha. A complementary silvicultural intervention took place three years later by harvesting commercial residual trees which were sawn in the forest by local smallholders with a frame-chainsaw and the resulting blocks hauled with an oxen. The cost of applying the silvicultural treatment was US$23,8/ha, including all inputs and manual labor. Total logging costs amounted US$1635 yielding an average of 4,3 m3 of timber per harvested hectare. The initial effects of the silvicultural interventions on forest dynamics were evaluated based on three periodic measurements of the population of trees 10+ cm dbh. In the four-year period after the silvicultural interventions mortality in the control plots was 11,2 trees/ha/year (4,9% of the original population), whereas in the treated plots it reached 20,3 tress/ha/year (2,4%). The median yearly increment in diameter was from 0,3 to 0,4 cm/year in the control plots and 0,3 to 0,5 cm/year in the treated plots. The median yearly diameter increments during the period oscillated between 0,3 and 0,5 cm.